Enhanced Performance of Transfer‐Free Graphene Transparent Conductive Films on Insulating Substrates by Introducing Array Nanostructure. Issue 13 (9th March 2023) - Lu, Meng; Zhang, Xiaoling; Yin, Wanying; Wang, Yao; Li, Dezeng; Zhao, Qingbiao
Abstract: Graphene is one of the most prevailing materials to replace traditional transparent conductive films (TCFs). In order to improve the performance of graphene TCFs, it is proposed to directly deposit graphene on insulating substrates via assisted catalysis of Cu foil to avoid intricate transfer process, and further effectively enhance the optical performance by introducing the close‐packed antireflection array nanostructure. The graphene TCFs grown on bare quartz substrates have sheet resistance of 0.766 kΩ sq −1 and transmittance of 86.83 %. Graphene composite TCFs with transmittance of 95.79 % were obtained by introducing the close‐packed solid/hollow SiO2 nanospheres antireflection array nanostructure. Compared with graphene TCFs, transmittance of graphene composite TCFs increased significantly, while the sheet resistance remained at the same level. This method combining direct synthesis technique with novel antireflection array nanostructure provides a significant design idea to grow transfer‐free graphene with controllable optoelectronic properties and promotes the application and development of the future electronic devices. Abstract : The transfer‐free graphene was directly deposited on insulating substrates by assisted catalysis of Cu foil. We further proposed an effective strategy to obtain graphene/AR composite TCFs with further improved optical performance by introducing a new type of c‐S/HSNSs antireflection array nanostructure while ensuring the electrical properties.